Brief Report: Preventing HIV-1 Infection in Women Using Oral Preexposure Prophylaxis. (15th December 2016) - Hanscom, Brett; Janes, Holly E.; Guarino, Peter D.; Huang, Ying; Brown, Elizabeth R.; Chen, Ying Qing; Hammer, Scott M.; Gilbert, Peter B.; Donnell, Deborah J.
Abstract : Abstract: The World Health Organization has issued an early release revision to its antiretroviral guidelines in which PrEP (pre-exposure prophylaxis in the form of daily oral, fixed dose combination tenofovir disoproxil fumarate/emtricitabine) is recommended as a prevention option to all people at substantial risk of acquiring HIV. However, lack of effectiveness in 2 major women-only PrEP trials, VOICE and FEM-PrEP, continues to be a cause for concern about achieving effectiveness for women in Southern Africa. We conducted a series of meta-analyses of oral effectiveness of tenofovir disoproxil fumarate/emtricitabine in women including all 5 randomized placebo-controlled trials that included women. An adherence-based meta-analysis model showed that with high levels of adherence (75%), oral PrEP is estimated to be effective (relative risk = 0.39, 95% confidence interval: 0.25 to 0.60). Provided that these results apply to women in Southern Africa, future prevention trial designs in that region should account for potentially reduced HIV incidence when PrEP is available.